Novel TP53RK variants cause varied clinical features of Galloway–Mowat syndrome without nephrotic syndrome in three unrelated Chinese patients - Chen, Jing; Ye, Gao-Bo; Huang, Jin-Rong; Peng, Min; Gu, Wei-Yue; Xiong, Pin; Zhu, Hong-min (Frontiers in Molecular Neuroscience, 2023)
Objectives: Galloway-Mowat syndrome-4 (GAMOS4), caused by the TP53RK gene mutations, is a very rare renal-neurologic disease characterized by early-onset nephrotic syndrome, microcephaly, and brain anomalies. So far, only eight cases with detailed clinical data, caused by seven deleterious variants in the TP53RK have been reported. This study aimed to examine the clinical and genetic characteristics of three unrelated patients with TP53RK gene compound heterozygous mutations. Methods: We identified four novel TP53RK variants using whole exome sequencing (WES) in three unrelated Chinese children. The clinical characteristics such as biochemical parameters and image findings of the patients were evaluated. Furthermore, we reviewed four studies of GAMOS4 patients with TP53RK variants and described the clinical and genetic features after a retrospective analysis of the clinical symptoms, laboratory data, and genetic test results. Results: The three patients all displayed facial abnormalities, global developmental delays, microcephaly, and aberrant cerebral imaging; patient 1 had slight proteinuria, while patient 2 had epilepsy. Nevertheless, none of the individuals had nephrotic syndrome and were still alive over three years old. The four identified variants in the TP53RK gene (NM_033550.4: c.16_17insAG/p.A6Efs*29, c.745A>G/p.R249G, c.185G>A/p.R62H and c.335A>G/p.Y112C) are unreported. Conclusions: The clinical characteristics of the three children deviate dramatically from the known GAMOS4 traits, early nephrotic syndrome, and predominantly mortality in the first year of life, which advances our understanding of this disease’s phenotype. This study expands the pathogenic TP53RK gene mutation spectrum and clinical phenotypes of GAMOS4.